Smart Helmet for Motorcyclist - Abd Wahab, Abdul Hadi; Mohamad, Muhamad Mukriz Shafiq; Mazlan, Muhammad Zulhilman; Mohd, Mohd Sabani (Multidisciplinary Applied Research and Innovation, 2022)
The Intelligent Smart Helmet for Motorcyclists is a project that aims to improve road safety. The concept came about because of a significant increase in deadly motorcycle accidents over the years. The accidents are thought to be caused by improper helmet use, such as not clipping the helmet string and riding the motorcycle in dark clothing, as well as being under the influence of alcohol. As a result, the goal of this project is to bring a whole new safety system to motorcycle riders. The motorcycle can only be started if the RF Transmitter and Receiver circuits detect an emission signal from the helmet. Collisions from behind the motorcycle can also be avoided with the use of the MQ-3 alcohol sensor on the helmet. The primary goal of this initiative is to increase motorcycle rider safety and reduce the frequency of fatal motorcycle accidents on the road.